(untitled) (Economia Aplicada, 1999)
This paper presents a survey of the literature on optimum currency areas. The theoretical debate on the issue is exposed and the adoption of the "euro" is discussed. Based on the theory and on the recent European case, some comments are made on the proposal of a currency union among the countries of Mercosul, officially mentioned by the Presidents of the region in 1998. It is concluded that such proposal makes sense as the final step of an integration process, but it will take a long time probably within 15 and 20 years - to transform it into reality, which will be conditioned to the fulfilling of several requirements.